Human and bacterial genetic variation shape oral microbiomes and health - Nolan Kamitaki; Robert E. Handsaker; Margaux L. A. Hujoel; Ronen E. Mukamel; Christina L. Usher; Steven A. McCarroll; Po-Ru Loh (Nature, 2026)
Abstract Human genetic variation influences all aspects of our biology, including the oral cavity 1–3 , through which nutrients and microbes enter the body. Yet it is largely unknown which human genetic variants shape a person’s oral microbiome and potentially promote its dysbiosis 3–5 . We characterized the oral microbiomes of 12,519 people by re-analysing whole-genome sequencing reads from previously sequenced saliva-derived DNA. Human genetic variation at 11 loci (10 new) associated with variation in oral microbiome composition. Several of these related to carbohydrate availability; the strongest association ( P = 3.0 × 10 −188 ) involved the common FUT2 W154X loss-of-function variant, which associated with the abundances of 58 bacterial species. Human host genetics also seemed to powerfully shape genetic variation in oral bacterial species: these 11 host genetic variants also associated with variation of gene dosages in 68 regions of bacterial genomes. Common, multi-allelic copy number variation of AMY1 , which encodes salivary amylase, associated with oral microbiome composition ( P = 1.5 × 10 −53 ) and with dentures use in UK Biobank ( P = 5.9 × 10 −35 , n = 418,039) but not with body mass index ( P = 0.85), suggesting that salivary amylase abundance impacts health by influencing the oral microbiome. Two other microbiome composition-associated loci, FUT2 and PITX1 , also significantly associated with dentures risk, collectively nominating numerous host–microbial interactions that contribute to tooth decay.